The Implementation of English Teachers’ Authentic Assessment in Junior High Schools - Prawisanthi, Tasya Astri; Dewi, Ni Luh Putu Eka Sulistia; Paramartha, A. A. Gede Yudha; Wahyuni, Luh Gede Eka (Universitas Pendidikan Ganesha, 2021)
The descriptive study identified the English teachers’ perceived knowledge of authentic assessment at SMP Negeri 3 Singaraja. In conducting the study, observations, questionnaire and interview guide were used. The data were analyzed using descriptive and interactive model analysis. It was found that English teacher at SMP Negeri 3 Singaraja has a good perceived knowledge of authentic assessment implementation. The types of authentic assessment used by the teacher were observation, performance, portfolio, project and peer. There was a discrepancy between teachers’ perceived knowledge and the implementation of authentic assessment. The discrepancy can be seen from the perceived knowledge and implementation of project assessment and peer/self-assessment. The implementation of authentic assessment in online learning were slightly different from face to face teaching. The teachers made certain adjustment for example in assessing students’ attitude in classroom. The attitude observation was adjusted in online learning based on students’ presence in online class and their responsibilities in doing tasks.